Therapeutic Insights into Maqāṣid al-Sharīʿah (Ultimate Objectives of Sharīʿah - Muideen Lateef, Abiola (Kashere Journal of Humanities, Management and Social Sciences, 2022)
Islam encourages legal development which establishes social justice that concerns itself with the well-being. Central to this legal development is the higher objectives of Sharīʿah or Maqāṣid al-Sharīʿah which advocatespurpose-based reading of the law in terms of well-being (Maṣlaḥah) of all. However, therapeutic framework of this legal development model is still lacking. There is an urgent need to develop this therapeutic model which sees the objectives of Sharīʿah as a healing and mercy to mankind. Using Al-Ghazāli’s Maqāṣid theory which gives priority to Five Essential Elements, this paper argues that Maqāṣid lens can be reconfigured to cater for, or at least pay attention to psychological issues affecting individual and social health, wealth, human relationships and well-being in all spheres of life.